Tác động của Chính sách chuyển đổi số với bảo vệ quyền tiếp cận thông tin - Diep, Nguyen Trong; Dat, Nguyen Tien (VNU Journal of Science: Legal Studies; Vol 38 No 3DO - 10.25073/2588-1167/vnuls.4444, 2022)
The right of access to information is one of the human rights, recognized by all nations of the world, based on the legislative recognition of the freedom of information in Sweden since 1766. This human right establishes the people’s trust and determines the political stability of each nation. This paper presents some basic contents and analyses the theoretical, practical and legal basis to ensure the right to access information in the era of digital transformation in Vietnam.